2009
DOI: 10.1111/j.1365-2672.2009.04343.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effects of specific bacterial components ofLactobacillus plantarumKFCC11389P on the murine macrophage cell line RAW 264·7

Abstract: Aims:  The objective of this study was to investigate the ability of specific bacterial components of Lactobacillus plantarum KFCC11389P to induce anti‐inflammatory mediators in cell cultures of the murine macrophage cell line, RAW 264·7. Methods and Results:  The RAW 264·7 cells were stimulated with viable bacterial cells (VC), heat‐killed (HK) cells, cell walls (CW) or ultrafiltrates of metabolic products (UF). An increase in the levels of tumour necrosis factor (TNF)‐α was observed in VC, HK and CW, but thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 36 publications
(55 reference statements)
4
35
0
Order By: Relevance
“…These results show that both the structural components and the soluble cellular content of lactobacilli have an important function in anti-inflammatory effects. This observation is consistent with previous studies, which suggested that live probiotics are not necessarily required for anti-inflammatory effects [15, 33, 34]. However, Ma et al suggested that only live Lactobacillus reuteri inhibit TNF- α -induced IL-8 production in T84 and HT-29 cells and the inhibitory effect was not reproduced using CM, bacterial lysates, and heat-killed or gamma-irradiated lactobacilli [31].…”
Section: Resultssupporting
confidence: 91%
“…These results show that both the structural components and the soluble cellular content of lactobacilli have an important function in anti-inflammatory effects. This observation is consistent with previous studies, which suggested that live probiotics are not necessarily required for anti-inflammatory effects [15, 33, 34]. However, Ma et al suggested that only live Lactobacillus reuteri inhibit TNF- α -induced IL-8 production in T84 and HT-29 cells and the inhibitory effect was not reproduced using CM, bacterial lysates, and heat-killed or gamma-irradiated lactobacilli [31].…”
Section: Resultssupporting
confidence: 91%
“…This suggests that the stimulus required for induction of IL‐10 is different from that of IL‐6, TNF‐α and IL‐1β and that some secreted component of the bacteria may be responsible for its induction (Chon et al . ). Similar observation was made by Suzuki et al .…”
Section: Discussionmentioning
confidence: 97%
“…L. plantarum HY115 may inhibit the production of NO in LPSstimulated RAW 264.7 cells [22]. The ultrafiltrates of L. plantarum KFCC11389P metabolic products inhibited the production of TNF-α and IL-6 in LPS-induced RAW 264.7 cells [23]. In this study, the in vitro anti-inflammatory capacities of K68 isolated from fu-tsai were assessed by measuring the levels of the pro-inflammatory mediators NO, TNF-α, and PGE 2 .…”
Section: Discussionmentioning
confidence: 98%